Apple juice for pediatric gastroenteritis. Issue 7 (July 2016) - Jarrett, Jennie B.
Abstract : N/A: Freedman SB, Willan AR, Boutis K, et al. Effect of dilute apple juice and preferred fluids vs electrolyte maintenance solution on treatment failure among children with mild gastroenteritis: a randomized clinical trial. JAMA . 2016; 315(18):1966–1974.